Representation of Women and Nature in the Movie Jigarthanda Double X : An Ecofeminist Analysis - S. Rupika (ILN Journal: Indian Literary Narratives, 2024)
This article analyses the representation of women and nature in Karthik Subbaraj's 2023 film Jigarthanda Double X through the lens of ecofeminism. Ecofeminism is a branch of feminism that examines the connections between women and nature. It posits that women and nature are linked through their shared experiences of oppression and exploitation under patriarchal structures. Cultural ecofeminism contends that women have a more intimate relationship with nature because of their gender roles (e.g., family nurturer and provider of food) and their biology (e.g., menstruation, pregnancy, and lactation). Drawing on ecofeminist theory, particularly cultural ecofeminist theory, this article explores how the narrative of this film intersects with the portrayal of female characters and natural environments, reflecting broader themes of gender, ecology, and power dynamics. Through an analysis of key scenes and character dynamics, the paper delves into how ecofeminist principles intersect with the narrative. It examines the character of Malaiarasi, whose deep-rooted connection to nature and traditional healing practices challenges conventional gender roles and emphasizes the importance of preserving indigenous ecological knowledge. Furthermore, the article examines scenes that depict the mistreatment of women and the exploitation of nature in the case of Paingili, drawing parallels between the two. Additionally, the paper analyzes the use of color symbolism and mise-en-scène elements to convey themes of life and exploitation in natural environments. This analysis demonstrates how Jigarthanda Double X employs cinematic techniques to emphasize the principles of ecofeminism, advocating for the empowerment of women and the protection of the environment as interconnected struggles for justice and equality.